THE PERSPECTIVE HUMAN DEVELOPMENT INDEX (HDI) : ROLE OF NUMBER OF POPULATION AND PERCAPITA INCOME - Suparjiman, Suparjiman; Fitriani, Iis Dewi; Kurnia, Ia (2020)
During the era of regional autonomy and fiscal decentralization, local governments were given the authority to increase their revenues and to carry out allocative functions in setting regional development priorities. This study aims to examine the effect of government spending, per capita income on the Human Development Index (HDI) in the district/city level of West Java Province. The study population consisted of 27 districts and municipalities, using secondary data from the Central Statistics Agency of West Java Province and Regency/City level of West Java Province in the 2017-2019 period. The results of this study indicate that income per capita has a positive effect on the human development index in the district/city level of West Java Province. Second, the population has an effect on the human development index in the district/city level of West Java Province.